2009
DOI: 10.1097/olq.0b013e31818d3fa0
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Increasing Prevalence of HIV and Syphilis and HIV-1 Subtype Characterization Among Men Who Have Sex With Men in Jiangsu, China

Abstract: The rapidly increasing prevalence and complex subtypes of HIV-1 suggest that effective prevention and intervention strategies are urgently needed for MSM in Jiangsu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 23 publications
6
49
1
Order By: Relevance
“…Our results were similar to those in the surrounding provinces (e.g., Shanghai, Anhui, and Shandong) (16)(17)(18), in which CRF01_AE appeared to be the most predominant HIV-1 genotype. However, the subtype distribution of HIV-1 among MSM in Zhenjiang was significantly different from that reported by Guo et al (12) in Jiangsu. They reported that 3 major subtypes including subtype B, CRF01, and B/C inter-subtype recombinants (especially CRF07) were circulating among MSM in Nanjing and Yangzhou, Jiangsu.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…Our results were similar to those in the surrounding provinces (e.g., Shanghai, Anhui, and Shandong) (16)(17)(18), in which CRF01_AE appeared to be the most predominant HIV-1 genotype. However, the subtype distribution of HIV-1 among MSM in Zhenjiang was significantly different from that reported by Guo et al (12) in Jiangsu. They reported that 3 major subtypes including subtype B, CRF01, and B/C inter-subtype recombinants (especially CRF07) were circulating among MSM in Nanjing and Yangzhou, Jiangsu.…”
Section: Discussioncontrasting
confidence: 52%
“…However, the HIV-HCV co-infection rate in Zhenjiang (0.2z) was lower than the prevalence (1.94z) among HIV-infected MSM in China (14). This showed that the HCV infection rate was still at a quite low level among HIV-infected MSM in China, especially in Jiangsu (0z) (12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it is estimated that 48,000 people have been newly infected with HIV, of whom more than 30z are infected via male homosexual transmission. These data indicate a rapid spread of the HIV epidemic among men who have sex with men (MSM) in China (2). Among the high-risk groups of HIV infection, MSM play an important role in transmitting HIV and other sexually transmitted infections (STIs) from their high-risk male sexual partners to their low-risk female partners (2), and unprotected sexual behaviors facilitate this transmission.…”
Section: Introductionmentioning
confidence: 99%